Bio-oil from rubber wood: effects of upgrading conditions - Nam, Nguyen Hong; Duc, Bui Van; Linh, Vu Ngoc; Ha, Vu Thi Thu; Pattiya, Adisak (Vietnam Journal of Science and Technology, 2020)
Despite its prominent potential, the use of rubber wood (Hevea brasiliensis) for bio-oil production has not been fully investigated. This study reported experimental results of the bio-oil production and upgrading from rubber wood using fast pyrolysis technology. The effects of catalyst nature (vermiculite and dolomite), upgrading temperature and bio-oil/catalyst ratio on the product quality were deeply investigated. The results showed that dolomite was suitable to be used as a catalyst for bio-oil upgrading. At 600 °C and a bio-oil/catalyst ratio of 1:1, the bio-oil yield was maximized, while at 400 °C and a ratio of 1:3, the bio-oil heating value was maximized. Depending on usage purposes, a yield-oriented, heating value-oriented or in-between bio-oil upgrading solution could be considered.